(untitled) (Research, Society and Development, 2024)
Autism spectrum disorder (ASD) is a developmental condition characterized by difficulties in social interactions and communication, repetitive and stereotyped behaviors, and a restricted repertoire of interests and activities. This work aimed to analyze the national scientific production on interventions carried out by school Physical Education Professionals with children with ASD, highlighting the most frequent approaches and the results that occurred. A comprehensive review of articles published between 2018 and 2022 was carried out. Data bases used were Google Scholar, VHL and SciELO databases. In total, 39 studies were identified, of which 9 met the inclusion criteria and were analyzed. These studies included different intervention strategies, including games and games, aquatic activities, rhythmic practices, trampoline exercises, and hippotherapy. The results suggest that physical activities can offer beneficial benefits for the development of children with ASD, promoting advances in communication, reducing antisocial, stereotypical, and aggressive behaviors, as well as improvements in motor progress and cognitive and emotional capabilities. Despite the promising effects mentioned, the national literature still lacks sufficient quantity and methodological quality to provide a solid support for decision-making on the role of the school education teacher in external multidisciplinary interventions for children with ASD.